Pathophysiologic basis of contrast enhancement in breast tumors - Knopp, Michael V.; Winkler, Eva C.; Sinn, Peter; Mattern, Jürgen; Junkermann, Hans; Radeleff, Jannis; Magener, Achim; Brix, Gunnar; Delorme, Stefan; Kaick, Gerhard van (Journal of magnetic resonance imaging, 1999)
While the diagnostic benefits of gadolinium (Gd)‐chelate contrast agents are firmly established in magnetic resonance imaging (MRI) of tumors, the pathophysiologic basis of the enhancement observed and its histopathologic correlate remained vague.
Gesehen am 18.02.2021